2022
DOI: 10.1021/acs.jpcb.2c03424
|View full text |Cite
|
Sign up to set email alerts
|

Crystallization of Flexible Chains of Tangent Hard Spheres under Full Confinement

Abstract: We present results from extensive Monte Carlo simulations on the crystallization of athermal polymers under full confinement. Polymers are represented as freely jointed chains of tangent hard spheres of uniform size. Confinement is applied through the presence of flat, parallel, and impenetrable walls in all dimensions. We analyze crystallization as the summation of two contributions: one that occurs in the bulk volume of the system (bulk crystallization), and one on the wall surfaces (surface crystallization)… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

4
14
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
5
2

Relationship

1
6

Authors

Journals

citations
Cited by 14 publications
(18 citation statements)
references
References 103 publications
4
14
0
Order By: Relevance
“…In spite of these difficulties, a wide variety of increasingly more efficient MC methods have been developed over the last few decades [ 78 , 79 , 82 , 83 , 84 , 85 , 86 , 87 , 88 ]. The work to be reported in this manuscript is based on a powerful suite of advanced MC moves [ 89 ], which in the past has enabled us to observe the entropy-driven athermal polymer crystallization for the first time [ 71 ], and to identify and analyze the factors that affect the phenomenon, including chain length and its distribution [ 71 , 90 ], the presence of bond gaps or tangency [ 91 ], and confinement in one [ 92 ] or all three [ 93 ] dimensions.…”
Section: Introductionmentioning
confidence: 99%
“…In spite of these difficulties, a wide variety of increasingly more efficient MC methods have been developed over the last few decades [ 78 , 79 , 82 , 83 , 84 , 85 , 86 , 87 , 88 ]. The work to be reported in this manuscript is based on a powerful suite of advanced MC moves [ 89 ], which in the past has enabled us to observe the entropy-driven athermal polymer crystallization for the first time [ 71 ], and to identify and analyze the factors that affect the phenomenon, including chain length and its distribution [ 71 , 90 ], the presence of bond gaps or tangency [ 91 ], and confinement in one [ 92 ] or all three [ 93 ] dimensions.…”
Section: Introductionmentioning
confidence: 99%
“…Site i is identified as an X-type crystal when the calculated CCE norm is lower than a critical threshold, ≤ . In past studies, an empirical threshold of 0.245 was determined for packings of non-overlapping spheres [41,95,96] in the bulk [40][41][42][43]55,56] and under confinement [44,45]. Due to the strict concept behind the descriptor, the CCE norm is highly discriminatory, so the value of a site cannot be simultaneously very low for two different reference crystals.…”
Section: Local Order: Characteristic Crystallographic Element Normmentioning
confidence: 99%
“…The mechanism of crystallization of hard colloidal polymers [37][38][39][40][41][42][43][44][45] differs substantially from that of traditional polymers, the latter as revealed in x-ray scattering studies of short alkane chains [46][47][48], and in MD [49][50][51][52] or MC [39,53] simulations. Just as for monomeric athermal hard spheres, off-lattice MC simulations have shown that random packings of fully flexible linear chains of tangent hard spheres are able to crystallize at high volume fractions through an entropy-driven mechanism, very similar to the one of monomeric analogs [37,[40][41][42]54].…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation
“…In spite of these difficulties, a wide variety of increasingly more efficient MC methods have been developed over the last decades [80,81,[84][85][86][87][88][89][90]. The work to be reported in this manuscript is based on a powerful suite of advanced MC moves [91] which has enabled us in the past to observe the entropy-driven athermal polymer crystallization for the first time [73] and to identify and analyze the factors that affect the phenomenon, including chain length and its distribution [73,92], the presence of bond gaps or tangency [93] and confinement in one [94] or all three [95] dimensions.…”
Section: Introductionmentioning
confidence: 99%